Fissure adjacent partial lobe atelectasis in primary ciliary dyskinesia. (16th November 2021) - Fabri, Loraine; Shanthikumar, Shivanthan; Tadd, Katelyn; Morgan, Lucy; Schultz, André; Robinson, Philip
Abstract : Aim: Establishing the underlying cause in a child with chronic suppurative lung disease (CSLD) allows for targeted treatment and screening for associated complications. One cause of CSLD is primary ciliary dyskinesia (PCD). Testing for PCD requires specialist expertise which is not widely available. Computed tomography (CT) scans are commonly performed when assessing CSLD. Identifying PCD‐specific signs on CT would help clinicians in deciding when to refer for specialist testing. One potential PCD‐specific sign we have observed is fissure adjacent partial lobe atelectasis (FAPLA). We aimed to assess if FAPLA is commonly found in CT of PCD patients. Methods: Fifty‐eight CT scans from 42 adult and child PCD patients were analysed. The presence and distribution of FAPLA were noted, and its association to sputum culture and other signs commonly seen in CSLD (bronchiectasis, bronchial wall thickening, air trapping and mucus plugging). Results: FAPLA was found in 13 of 40 participants in their earliest CT scan. The prevalence of FAPLA was similar in children and adults. FAPLA involved the right middle lobe in all 13 cases and was systematically associated with ≥1 other structural change. There was no association between FAPLA and bacterial isolation from sputum. Conclusion: FAPLA was found in 32.5% PCD scans, without difference between children and adults in terms of frequency. Future work will determine if it is a PCD‐specific sign by assessing whether it is also found in other CSLD processes and analysing more scans from children with PCD to determine how early this sign develops.